Assessing the effect of cesarean section on Crohn’s Disease - Gagnon, Pascale (Université d'Ottawa | University of Ottawa, 2017)
Background: Crohn's disease is a chronic inflammatory disease whose incidence is increasing in industrialized countries. The causes of the disease are unclear, but the interaction between environmental and genetic factors would be involved. In a perinatal context, the hypothesis of hygiene and the early bacterial colonization of the newborn would be a causal factor very plausible. Objective: to evaluate the effect of cesarean delivery on the subsequent development of Crohn's disease in industrialized countries. Methods: A literary census was completed using the MEDLINE database and reference lists of articles identified from 2000. Only RCT, cohort studies and case-control studies, peer-reviewed and employing a comparison group were selected. Studies that did not make the clear distinction between Crohn's disease and other inflammatory bowel diseases were excluded as well as studies investigating mothers with Crohn’s disease. Results: A total of 8 studies meeting the eligibility criteria were selected. Although only two of the studies showed positive association, the summative review of all studies reveal no significant effect of caesarean births in the increase of Crohn's disease cases. However, these results are potentially overestimated. Since four of the publications were case-control studies, the selection of participants was based on the presence of the disease, thus introducing a possible source of bias. In addition, misclassification of participants is likely for two reasons: first, the criteria used for the diagnosis of Crohn's disease were different for some studies, and second, the similarity between the diagnostic criteria for Crohn's disease and those for ulcerative colitis can be confusing, thus biasing the results. Conclusion: The results demonstrate that caesarean births are not associated with an increased risk of developing Crohn's disease. However, because of the presence of potential cofounding, more research are needed.